"Life or death": Experiences of insulin insecurity among adults with type 1 diabetes in the United States. (August 2020) - Willner, Samantha; Whittemore, Robin; Keene, Danya
Abstract: Objective: Insulin access for people with diabetes is a growing public health concern and particularly important for people with type 1 diabetes (T1D) who depend on insulin for survival. However, few studies have examined the psychosocial contexts in which people with T1D confront, navigate, and attempt to resolve insulin access barriers (IABs). We conducted a qualitative study to: 1) describe factors affecting insulin access among adults with T1D, 2) characterize behavioral and emotional responses to IABs, and 3) understand the overall impact of IABs on the lives of adults with T1D. Methods: We recruited a geographically and age diverse sample of U.S. adults with T1D ( n = 21) from online diabetes support groups who self-identified as facing IABs. We conducted semi-structured phone interviews lasting 45–60 min between April and October 2017. We followed an inductive coding approach to identify concepts and themes related to participants' experiences with IABs. Findings: Participants conceptualized the experience of being without insulin as a "life or death" emergency, which significantly influenced their subsequent behavioral and emotional responses to compromised insulin access. Participants also described multiple IABs including unaffordable health care, institutional unresponsiveness, and major life transitions. Unable to consistently depend on the U.S. healthcare system to address their insulin needs, participants described taking strategic actions to maximize their existing insulin supplies, obtain more insulin, and create long-term security against future IABs. These strategies were not always successful and often negatively impacted participants' health, finances, careers, relationships, and future opportunities. Conclusions: Disruptions in insulin access or the threat of future disruption, a concept we term "insulin insecurity, " is a barrier to health and well-being among people with T1D. Our findings suggest the U.S. healthcare system is ill-equipped to address insulin needs among adults with T1D. Highlights: "Insulin insecurity" is a significant barrier to well-being among U.S. adults with type 1 diabetes (T1D). High costs of insulin and healthcare in the U.S. are major barriers to insulin access. Insulin insecure people with T1D may resort to extreme, risky measures to access insulin. Existing policies, resources, and programs are inadequate for addressing insulin insecurity. Immediate measures should be taken to create a safety net for insulin insecure Americans with T1D.